Interpretation in Ásbyrgi: Communicating with National Park Visitors in Iceland - Georgette Leah Burns; Laufey Haraldsdóttir; Guðrún Þóra Gunnarsdóttir (Sustainability, 2021)
Iceland has experienced rapid increases in tourism in recent years. This growth earns economic applause, but can come at considerable environmental cost. As Iceland’s unique environment is a drawcard for many tourists, careful management of destinations to ensure a sustainable environment is critical. The Icelandic Government is aware of the need for effective destination management and planning to ensure a sustainable future for tourism development, and the need to couple this with visitor compliance. It is a development that cannot be divorced from the need for environmental sustainability, and responsibility for this lies with all tourism stakeholders. One management tool to assist with such responsibility and compliance in tourism is interpretation: creating and delivering messages to visitors that enhance not only their satisfaction with an experience but also their understanding of it. This paper is based on an evaluation of visitors’ experiences and managers’ perceptions, as is necessary to ensure visitor satisfaction, while determining how best to maintain a sustainable environment. By observing and interviewing visitors, guides, rangers, and managers at Ásbyrgi in the northernmost part of Vatnajökull National Park, Iceland, we were able to discover what sort of information park visitors want to receive, what park managers want to convey, and the preferred way to deliver that information. Overall, most visitors and guides were satisfied with the interpretation in Ásbyrgi and preferred information provided verbally by guides or rangers over other types, such as on signs or in electronic format. Visitors want information about the unique geology and cultural history, as well as directional instructions for hiking trails. Managers want to create an accessible space in which visitors comply with instructions about safety and environmental sustainability. These findings can assist tourism management in Ásbyrgi, and other nature-based destinations, particularly in terms of sustainability of the natural ...